2017
DOI: 10.1007/s00221-017-4924-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in postural tremor dynamics with age and neurological disease

Abstract: The overlap of dominant tremor frequencies and similarly amplified tremor observed for Parkinson's disease (PD) and essential tremor (ET) means differentiating between these pathologies is often difficult. As tremor exhibits non-linear properties, employing both linear and non-linear analyses may help distinguish between the tremor dynamics of aging, PD and ET. This study was designed to examine postural tremor in healthy older adults, PD and ET using standard linear and non-linear metrics. Hand and finger pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…Our results showed that inter-hand coherence and peak coherence were larger in the PD group than in the REF group. At first, this seems to be in contrast to a recent finding by Morrison et al of no difference of peak coherence of postural hand tremor accelerations between persons with PD having bilateral tremor and healthy peers [39]. However, this discrepancy may be caused by analytic differences, as our analyses were specified to the parkinsonian tremor band (4–7 Hz extended by 1 Hz to 3–8 Hz) to focus the analysis.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Our results showed that inter-hand coherence and peak coherence were larger in the PD group than in the REF group. At first, this seems to be in contrast to a recent finding by Morrison et al of no difference of peak coherence of postural hand tremor accelerations between persons with PD having bilateral tremor and healthy peers [39]. However, this discrepancy may be caused by analytic differences, as our analyses were specified to the parkinsonian tremor band (4–7 Hz extended by 1 Hz to 3–8 Hz) to focus the analysis.…”
Section: Discussioncontrasting
confidence: 59%
“…The study by Morrison et al included tremor frequencies up to 40 Hz and thus included frequencies of both the parkinsonian and physiological tremor bands. Morrison et al found that 75% of the accumulated proportional tremor power in the healthy group extended up to 10–11 Hz while it was found below 5–6 Hz in the PD group [39]. In addition, they found the mean frequency of peak coherence for the healthy group to be 8.9 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of most tremor studies is detecting or comparing the tremor of different groups/conditions and extracting features of the whole signal [ 10 , 20 , 26 , 27 , 35 , 36 ]. However, to identify underlying patterns in tremor signals, it is necessary to track them since tremors change over time.…”
Section: Discussionmentioning
confidence: 99%
“…The first component is subject to mechanical resonance at the eigenfrequency of the oscillating limb. This mechanical resonance may simultaneously oscillate the limb by recruiting the motor unit, and this rhythm is a feedback system into the spinal reflex loops, which could enhance the tremor [ 37 ]. The second component, in the 8-12 Hz range, is driven by the central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%